Shifting Boundaries: Women's Career Empowerment Through Flexibility in Hotels - Dyah Palupiningtyas; Krisnawati Setyaningrum Nugraheni; Dita Aulia Rachma Nurul Farida (Denasya Smart Publisher, 2025)
This study employs Interpretative Phenomenological Analysis (IPA) to explore the lived experience and subjective meaning of work flexibility for women's career empowerment in star-rated hotels in Semarang. Eight female employees from various departments of 3-5 star hotels participated in semi-structured in-depth interviews. The analysis generated four superordinate themes: (1) the meaning of work flexibility in the hotel context, (2) work-family balance negotiation strategies, (3) psychological empowerment through flexibility, and (4) women's career barriers. Findings reveal that in the 24-hour hospitality industry, work flexibility is primarily understood as control over shift schedules rather than location flexibility. Access to schedule flexibility enhances all four dimensions of Spreitzer’s psychological empowerment: meaning, competence, self-determination, and impact. Self-determination emerged as the most affected dimension, where the ability to manage work schedules increased perceptions of autonomy and life control. Supervisor support as border-keepers and female solidarity play crucial roles in work-family balance negotiation. However, glass ceiling barriers and gender stereotypes remain persistent. This research provides a novel theoretical integration of work-family border theory and psychological empowerment theory, offering practical implications for gender-sensitive HR policy development in the hotel industry.Keywords: Hospitality Industry; Interpretative Phenomenological Analysis; Work Flexibility, Psychological Empowerment; Women's Career.